2016
DOI: 10.1155/2016/4078695
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Assessing the Efficacy of Gabapentin Plus B Complex (B1/B12) versus Pregabalin for Treating Painful Diabetic Neuropathy

Abstract: Introduction. Painful diabetic neuropathy (PDN) is a prevalent and impairing disorder. The objective of this study was to show the efficacy and safety of gabapentin (GBP) plus complex B vitamins: thiamine (B1) and cyanocobalamine (B12) compared to pregabalin in patients with moderate to severe intensity PDN. Method. Multicenter, randomized, blind study. Two hundred and seventy patients were evaluated, 147 with GBP/B1/B12 and 123 with PGB, with a 7/10 pain intensity on the Visual Analog Scale (VAS). Five visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
(30 reference statements)
1
9
0
7
Order By: Relevance
“…As described by several previous non‐randomized trials, our study result showed that gabapentin was well tolerated with acceptable safety profile similar to the placebo group . Particularly, the safety profile for gabapentin was already well established in several large studies used to treat other neurologic conditions . However, gabapentin is rarely used in the treatment of lower urinary tract symptoms due to concerns over some serious adverse effects such somnolence and neurologic adverse events .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As described by several previous non‐randomized trials, our study result showed that gabapentin was well tolerated with acceptable safety profile similar to the placebo group . Particularly, the safety profile for gabapentin was already well established in several large studies used to treat other neurologic conditions . However, gabapentin is rarely used in the treatment of lower urinary tract symptoms due to concerns over some serious adverse effects such somnolence and neurologic adverse events .…”
Section: Discussionsupporting
confidence: 72%
“…Particularly, the safety profile for gabapentin was already well established in several large studies used to treat other neurologic conditions . However, gabapentin is rarely used in the treatment of lower urinary tract symptoms due to concerns over some serious adverse effects such somnolence and neurologic adverse events . Our trial showed that patients treated with gabapentin experienced common associated mild forms of neurologic effects such as dizziness and headache.…”
Section: Discussionmentioning
confidence: 70%
“…Анальгетический эффект витаминов группы В в наше время уже не ставится под сомнение, в многочисленных исследованиях [25][26][27] доказана необходимость комплексной терапии с их участием в лечении болевых синдромов, сопровождающихся сенсорными нарушениями. За последнее время показана эффективность комплексной терапии НБ при применении габапентина и витаминов группы В. В частности, A. Mimenza и S. Aguilar [28] в 2016 г. провели исследование с применением антиконвульсантов и витаминов В 12 /В 1 у больных с диабетической полинейропатией. В течение 12 нед пациенты с болевой формой диабетической полинейропатии принимали терапию по двум схемам: габапентин 300-3600 мг + В 12 (0,2 мг)/В 1 (100 мг) и прегабалин 75-600 мг.…”
Section: Discussionunclassified
“…Персонифицированная терапия Габагаммой ® способствует быстрому эффективному обезболиванию, предотвращению выраженных побочных эффектов и хорошему комплаенсу. В рандомизированных клинических исследованиях показано, что комбинация габапентина с витаминами группы В дает возможность уменьшить дозу габапентина [22].…”
unclassified